Chapter Ralf Dahrendorf. Società dell’attività, lavoro e chances di vita - LEONARDI, LAURA (Firenze University Press, 2025)
Ralf Dahrendorf analyses in an original way the relationship between labour and active freedom within the theoretical frame of life chances. He starts from the observation that the new challenge for today's societies is how to guarantee an existential basis for people without a stable employment, since social citizenship is still rooted in the assumptions of the labour society that has lost centrality. The problem of an unequal distribution of work opportunities is evident. The result is the "decline in life chances for many". He argues that the answer can be found in the construction of a society of activity, in which work for the market is no longer pervasive of every sphere of life but leaves room for the multiple expressions of agency. The society of activity is thus configured as the structural context in which it is possible to reactivate the forms of cooperative conflict that allow the expansion of life chances.